PENYUSUNAN RENCANA STRATEGIS DALAM PENGEMBANGAN BUDAYA MUTU PENDIDIKAN DI SEKOLAH TINGGI AGAMA ISLAM SYEKH H. ABDUL HALIM HASAN AL ISHLAHIYAH BINJAI - Syafaruddin Syafaruddin; Mesiono Mesiono; Muhammedi Muhammedi (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
Formulating a strategic plan in developing a culture of quality education at the Islamic High School of Sheikh H. Abdul Halim Hasan Al Ishlahiyah Binjai by: first, formulating the vision, mission, and goals; second, forming a Strategic Plan Drafting Team; third, the formulation process; and fourth, the ratification of the strategic plan. The Strategic Plan Drafting Team consists of the Head of STAI, Deputy Chair, Head of the Quality Assurance Unit, Ka. Study programs, and lecturers. Each party involved in formulating programs and strategies in accordance with their respective fields and for educational quality goals manages facilities, from procurement, maintenance and repair, to development that can create a clean, neat, and beautiful campus environment so as to create pleasant conditions. both for lecturers and students to be on campus. Preparation of strategic programs, namely the development of study programs, facilities and infrastructure, governance and management, development of human resources (HR), funds and funding, quality assurance, research, community service, and cooperation by developing a quality culture, namely: open and continuous communication, mutually supportive internal partnerships, teamwork, discipline, and responsibility. The next step is to socialize it to stakeholders, the academic community, and public and private agencies so that the strategic plan that has been prepared will be successful.